Umbilical cord bilirubin level and pre-discharge hyperbilirubinemia risk. (3rd April 2021) - Zanardo, Vincenzo; Simbi, Alphonse K.; Parotto, Matteo; Guerrini, Pietro; Severino, Lorenzo; Ferro, Sergio; Straface, Gianluca
Abstract: Objectives: To assess whether arterial umbilical cord bilirubin (aUCB) level at delivery predicts predischarge neonatal hyperbilirubinemia, facilitating a safe discharge from the hospital. Methods: Prospective analysis of hospital biochemistry records identified near term and term infants with recorded aUCB and predischarge, at 36 h of life, capillary heal bilirubin (cHB), to identify those with a cutoff of bilirubin levels >9 mg/ml, >75th percentile on the nomogram of Bhutani et al. Results: Of 616 study neonates, median (IQR) aUCB and cHB levels were 1.5 mg % (IQR 0.7–2.2) and 7.7 mg % (IQR 6.6–8.9), respectively. The values resulted statistically correlated (Pearson correlation coefficient 0.26, p  < .0001) and an increment of 1 mg/dl in aUCB was associated with an increment (Regression coefficient, 95% confidence interval) of mean cHB 0.49 (0.33–0.65, p  < .0001). Among these, 143 (23.2%) neonates developed bilirubin levels >9 mg/ml at 36 h of life and multivariable analysis confirmed that cHB levels (OR 1.49, 95% CI 1.22–1.82; p  < .0001) and vaginal delivery (OR 2.34, 95% CI 1.33–4.36; p  = .005) were significantly associated with bilirubin levels >9 mg/ml. Conclusions: These data suggest that aUCB should be added to the list of major risk factors for neonatal hyperbilirubinemia.